Stock Status Assessment of Diplodus sargus (L., 1758) in the Syrian Marine Waters (Banyas Coast) - حسين شيرين; إبراهيم أمير; لحلح مرهف; الشاوي فراس (Latakia University Journal -Biological Sciences Series, 2021)
The estimation of fish stocks is an important part of fisheries management and the study of economic fish stocks is the main goal of any fisheries’ assessment process; as this supports the social and economic stability of fishermen. Diplodus sargus (Linnaeus, 1758) is one fish species of Sparidae family, and it is an important economic fish in the catch. The stock assessment of Diplodus sargus in Banyas coast had been studied. The results showed that D. sargus population was distributed into six age groups, growth was allometric (b=3.2), Von Bertalanffy parameters were (K=0.3/year, L∞=31.15 cm, t0= -0.35/year), Y/R =15.38g, and B/R=33.48g. Thus, the stocks of D. sargus is suffering from overfishing and overexploitation.